Overmodulation and field weakening in direct torque control of induction motor drives - Ahmad, Md. Zarafi (2006)
During transient conditions, for instance during acceleration and deceleration, the inverter used in an induction motor drive normally operates in overmodulation in order to efficiently utilize the DC-link voltage. Beyond the based-speed, the flux is normally reduced proportionally with speed to extend the speed range of the drive system. The capability of the induction motor drive under overmodulation and field weakening modes are important, especially in electric vehicle applications, where the available power is limited and the speed range needs to be increased to avoid use of the mechanical gear. In order to fully utilize the dc link voltage, it is important to understand the characteristics and performance of the drive system under these conditions. The project will perform a simulation study on the performance of direct torque control (DTC) induction motor drive under overmodulation and field weakening conditions. In this project the study on overmodulation and field weakening modes will be concentrated mainly on constant frequency torque controller-based DTC drive. The potential of the constant frequency torque controller in overmodulation and field weakening regions will be analyzed through simulation using Matlab/Simulink package. The results obtained from the simulation is evaluated.